Transformasi Transformasi Strategi Pembinaan Mutu Akademik Mahasiswa Penerima KIP-Kuliah Berbasis Boarding Campus: Peningkatan Kualitas Belajar, Peningkatan Kualitas Pengabdian Masyarakat, Peningkatan Kualitas Pengajar, Peningkatan Layanan dan Fasilitas, Dampak Transformasi Strategi Terhadap Pembinaan Mutu Akademik Mahasiswa - Rafika Anggraini; Riyuzen Praja Tuala; M. Kharis Fadillah (Universitas Hamzanwadi, 2025)
Strategic transformation usually involves comprehensive changes in the way an organization operates, with a focus on larger long-term goals. Therefore, it requires in-depth research and studies to determine whether the transformation effectively contributes to the development of students' academic quality. This research was conducted using qualitative methods. Data collection was carried out using observation, interviews, and documentation methods. The method in data analysis is carried out by reducing data, presenting data, and drawing conclusions. The objectives to be achieved in this research include: (1) To understand and analyze how the transformation of strategies implemented by the Mudir (Dormitory Head) in fostering the academic quality of KIP-Kuliah students living in the dormitory; (2) To understand and analyze the impact of the strategy transformation on the academic quality development of KIP-Kuliah students in the dormitory. From this research, it was found that: (1) The transformation of strategies implemented by the Mudir in academic quality development includes: a) Improvement of learning quality by utilizing technological advancements, halaqah ta’lim, and the use of learning applications, b) Improvement of community service quality, c) Improvement of teacher quality, d) Improvement of services and facilities. (2) The transformation of these strategies has a positive impact on students' academic achievements, as evidenced by the numerous awards won in various competitions and an average GPA above 3. 25